Determination of Lead Levels in Fuel Used for Vehicles in Baghdad City - Hassoon, Hassanein A. (Iraqi Journal of Science, 2019)
The wide use of lead compounds as an engine anti-knock reflects conversely on all components of the ecosystem. This study aimed to detect the concentration of lead in various types of gasoline and gas oil that are highly consumed by vehicles. Eight fuel samples were collected from different feul stations distributed in different districts of Baghdad city. These included two gas oil (diesel) stations and three stations for each type of gasoline (leaded and unleaded). Lead was extracted by the modified chemical method, and then flame atomic absorption technique was applied to assay its concentrations. The results indicated that lead levels were within permitted limits (150 mg Lead L-1) recommended by the international agencies. The highest lead mean concentration was 105 mg/L, recorded in Latifiya leaded gasoline, whereas the lowest mean was 3.1mg/L in unleaded gasoline imported from the United Arab Emirate. As for gas oil, lead concentration occurred within a mean of 1.85-2.05 mg/L. The influence of some leaded gasoline improvements, octane booster and octane plus, was estimated, which revealed sharp declines in lead mean concentrationsto values of 1.05 and 5.2 mg/L for Latifiya and Rusafa gasoline, respectively. Furthermore, the daily lead emission was estimated for the registered vehicles in Baghdad and revealed a high concentration of 1837.7 Âµg lead m-3 for private cars. This study proposes avoiding the addition of lead compounds to fuel, in order to reduce its adverse effects on general health, and raising the awareness of society to this problem.